2017
DOI: 10.1002/cbic.201600685
|View full text |Cite
|
Sign up to set email alerts
|

P450 BM3‐Catalyzed Regio‐ and Stereoselective Hydroxylation Aiming at the Synthesis of Phthalides and Isocoumarins

Abstract: Cytochrome P450 BM3 monooxygenases are able to catalyze the regio- and stereoselective oxygenation of a broad range of substrates, with promising potential for synthetic applications. To study the suitability of P450 BM3 variants for stereoselective benzylic hydroxylation of 2-alkylated benzoic acid esters, the biotransformation of methyl 2-ethylbenzoate, resulting in both enantiomeric forms of 3-methylphthalide, was investigated. In the case of methyl 2-propylbenzoate as a substrate the regioselectivity of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Systematic sequence-based literature mining analysis showed that residue of standard position 87, located within SRS1, is the most frequently investigated residue position for all CYPs [ 37 ]. This position (F87) is especially well-known from P450BM3, for which substitutions of F87 cause significant changes in the substrate spectrum towards unnatural substrates that include aromatic compounds, alkanes, and pharmaceuticals, with enhanced regio- and stereoselectivity, improved catalytic rates, and increased total turnover [ [40] , [41] , [42] , [43] ].…”
Section: “Hotspots” For Rational and Semi-rational Engineeringmentioning
confidence: 99%
“…Systematic sequence-based literature mining analysis showed that residue of standard position 87, located within SRS1, is the most frequently investigated residue position for all CYPs [ 37 ]. This position (F87) is especially well-known from P450BM3, for which substitutions of F87 cause significant changes in the substrate spectrum towards unnatural substrates that include aromatic compounds, alkanes, and pharmaceuticals, with enhanced regio- and stereoselectivity, improved catalytic rates, and increased total turnover [ [40] , [41] , [42] , [43] ].…”
Section: “Hotspots” For Rational and Semi-rational Engineeringmentioning
confidence: 99%
“…P450 enzymes have been extensively studied and engineered for the selective oxidation of diverse substrates for synthetic applications. Along with wild-type P450s, which are capable of regio- and stereoselective oxidations with high activity, , these enzymes were successfully optimized by means of protein engineering. Engineered P450 variants were constructed using directed evolution, , site-directed mutagenesis, site-saturation mutagenesis, and combinatorial active-site saturation tests (CASTs). , In our attempt to increase the CYP154E1 activity toward ( S )-ketamine and simultaneously construct a highly selective variant, we applied first-sphere mutagenesis focusing on amino acid substitutions at positions located at a distance of fewer than 15 Å from the heme iron. The first-sphere mutagenesis has been successfully used by our and other research groups to increase the activity and selectivity of different P450 enzymes. , This strategy is based on the hypothesis that positions in the first sphere of the heme iron are likely to interact with any substrate and hence influence its orientation and thereby the regio- and stereoselectivity of the enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…Further studies by the group focused on the enantioselective benzylic hydroxylation of benzoic acid derivatives by P450BM3 variants in pursuit of phthalide and isocoumarin products. 40 Methyl-2-ethylbenzoate 28 was converted to isocoumarin 29 with ( R )- or ( S )-selectivity using the R47Y or F87V/L188Q variants, respectively, with 79 and 70% conversion. The reaction with R47Y was scaled up to 2.20 mmol in 210 mL to give the ( R )-product in 32% isolated yield and 66% ee.…”
Section: Cytochromes P450mentioning
confidence: 99%